Can the concept of the protean career help us to understand millennial pre-service teacher retention challenges? A study of two pre-service teachers' career pathways in England. Issue 3 (26th May 2020) - Parfitt, Anne
ABSTRACT: The career pathways of two pre-service teachers on the point of entering the school workforce were investigated to inform debates on teacher retention. Narrative data were analysed to explore the orientations of two Millennials completing a university-led initial teacher education programme. The protean career concept sheds light on a mindset regarding career pathways that is substantially different to that espoused by earlier generations of teachers, for whom a working life carried out within the profession could have been a realistic proposition. However, this study demonstrated that the concept cannot be applied universally to a cohort. When considering the two case study participants' narratives, it was necessary to employ elements of a capabilities analysis approach to explore their distinct outcomes after they had initially pursued their goal of 'making a difference' and realised that they were unlikely to achieve this through teaching.